2002
DOI: 10.1007/s00210-001-0527-5
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-day dependent pharmacodynamic and pharmacokinetic profiles of caffeine in rats

Abstract: This study aims to investigate the effects of caffeine on the daily rhythms of heart rate (HR), body temperature (BT) and locomotor activity (LA) in rats in relation to time-of-day of administration, as well as their possible mechanisms, particularly related to caffeine pharmacokinetics. During the pharmacodynamic study, HR, BT and LA were measured every 10 min by radiotelemetry and analysed by Cosinor. This study was divided into three periods: a control period P1, a treatment period P2 and a recovery period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Moreover, results may be misleading, e.g. certain drug's toxicity [89][90][91], or mortality [92][93][94], or intensity of some pharmacological action [91,[95][96][97][98][99][100][101][102] may vary with time of day, even when in vitro tissue preparations are performed [103,104]. Thus, circadian rhythms and biological time must be considered when designing experiments and interpreting data.…”
Section: Biological Rhythms In Biological Data: a Potential Source Ofmentioning
confidence: 99%
“…Moreover, results may be misleading, e.g. certain drug's toxicity [89][90][91], or mortality [92][93][94], or intensity of some pharmacological action [91,[95][96][97][98][99][100][101][102] may vary with time of day, even when in vitro tissue preparations are performed [103,104]. Thus, circadian rhythms and biological time must be considered when designing experiments and interpreting data.…”
Section: Biological Rhythms In Biological Data: a Potential Source Ofmentioning
confidence: 99%
“…Pelissier‐Alicot et al (2002) investigated the effects of caffeine on the daily rhythms of heart rate, body temperature, locomotor activity, and caffeine pharmacokinetics (PK) in 10‐week‐old male Wistar rats in relation to time‐of‐day. The study was divided into three 7‐day phases: a control period, a treatment period, and a recovery period.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Its metabolism depends on the gender, age, physiological state of the organism, the use of oral contraceptives and smoking [1,2,3]. The pharmacokinetics of caffeine, in addition to the organism's ontogenic characteristics, are also affected by external physical factors, such as temperature and the time of day of its consumption [4,5]. The relationship between an individual's activity and the time of day the caffeine was administered was observed by Pelissier-Alicot et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetics of caffeine, in addition to the organism's ontogenic characteristics, are also affected by external physical factors, such as temperature and the time of day of its consumption [4,5]. The relationship between an individual's activity and the time of day the caffeine was administered was observed by Pelissier-Alicot et al [4]. A study on rats found that the effect of caffeine on the heart rate, locomotor activity and daily body temperature cycle is more marked when administered in the morning.…”
Section: Introductionmentioning
confidence: 99%